Paediatric aortic valve replacement using decellularized allografts. (22nd May 2020) - Horke, Alexander; Bobylev, Dmitry; Avsar, Murat; Meyns, Bart; Rega, Filip; Hazekamp, Mark; Huebler, Michael; Schmiady, Martin; Tzanavaros, Ioannis; Cesnjevar, Robert; Ciubotaru, Anatol; Laufer, Günther; et al.
Abstract: OBJECTIVES: Options for paediatric aortic valve replacement (AVR) are limited if valve repair is not feasible. Results of paediatric Ross procedures are inferior to adult Ross results, and mechanical AVR imposes constant anticoagulation with the inherent risks. METHODS: The study design was a prospective, multicentre follow-up of all paediatric patients receiving decellularized aortic homografts (DAHs) for AVR in 8 European centres. RESULTS: A total of 106 children (77 boys) were operated (mean age 10.1 ± 4.8 years, DAH diameter 20.5 ± 3.8 mm). A total of 60 (57%) had undergone previous surgical interventions: 34 with 1, 15 with 2 and 11 with ≥3. There was one early death in a 12-year-old girl, who underwent her fourth aortic valve operation, due to intracerebral haemorrhage on extracorporeal membrane oxygenation after coronary reimplantation problems following 3-sinus reconstruction 1 year earlier. One 2-year-old patient died due to sepsis 2 months postoperatively with no evidence for endocarditis. In addition, a single pacemaker implantation was necessary and a 2.5-year-old girl underwent successful HTx due to chronic myocardial failure despite an intact DAH. After a mean follow-up of 3.30 ± 2.45 years, primary efficacy end points mean peak gradient (18.1 ± 20.9 mmHg) and regurgitation (mean 0.61 ± 0.63, grade 0–3) were very good. Freedom from death/explantation/endocarditis/bleeding/stroke at 5 years was 97.8 ± 1.6/85.0 ± 7.4/100/100/100% respectively. Calculated expected adverse events were lower for DAH compared to cryopreserved homograft patients (mean age 8.9 years), lower than in Ross patients (9.4 years) and in the same range as mechanical AVR (12.8 years). CONCLUSIONS: Even though the overall number of paediatric DAH patients and the follow-up time span are still limited, our data suggest that DAHs may present a promising additional option for paediatric AVR.